Acute Effects of Aqueous Leaf Extract of Aspilia Africana C.D. Adams on Some Haematological Parameters in Rats - Ajeigbe, Kazeem Olasunkanmi (African Networks on Ethnomedicines, 2013)
Several medicinal plants have been documented for their haematological effects either at low or high concentration but very little is known about Aspilia africana. The aim of the study was to investigate the acute effects of aqueous leaf extract of Aspilia africana at different concentrations on some haematological parameters in rats. Following 14 days of oral administration of aqueous extract of A. africana, Haematocrit (HCT), Haemoglobin concentration (HB), Mean Cell Haemoglobin Concentration (MCHC), Red Blood Cell Count (RBC Count), Total White Blood Cell Count (Total WBC Count), Absolute Neutrophils count (NEUT#), Absolute Lymphocytes count (LYM#), Absolute Eosinophils Count (EOSIN#) and Absolute Monocytes (MONO#) were evaluated in twenty (20) male Wistar albino rats. The rats weighed 174±20g, and were randomly assigned into 4 groups viz: Group 1, Control; Group 2, 250mg/Kg/d aqueous extract; Group 3, 500mg/Kg/d aqueous extract; and Group 4, 750mg/Kg/d aqueous extract. HCT, HB, MCHC, RBC Count, Total WBC Count, NEUT#, LYM#, EOSIN# and MONO# were significantly increased (P<0.001) in 500mg/Kg/d of A. africana extract (61.13±1.65%, 13.5±1.29g/dl, 23.33±0.0.02g/dl, 3.68±0.02 X 10(12)Cells/l, 2.33±0.02 X 10(9)Cells/l, 1.32±0.04 X 10(9)Cells/l, 1.43±0.05 X 10(9)Cells/l, 0.47±0.02 X 10(9)Cells/l and 0.47±0.04 X 10(9)Cells/l, respectively) when compared to the Control (51.13±0.85%, 9.56±0.43g/dl, 19.22±0.19g/dl, 2.69±0.01 X 10(12)Cells/l, 1.79±0.01 X 10(9)Cells/l, 0.80±0.00 X 10(9)Cells/l, 0.83±0.00 X 10(9)Cells/l, 0.18±0.00 X 10(9)Cells/l and 0.24±0.00 X 10(9)Cells/l, respectively) which received no extract at all. The 500mg/Kg of A. africana extract proved to be the most effective, while the 750mg/Kg proved to be the least effective in comparison with the control. The results of this study further strengthened the earlier works on the medicinal benefits of Aspilia africana and its virtue as a good pharmacological source of haematopoiesis.